Collagen-Containing Fish Sidestream-Derived Protein Hydrolysates Support Skin Repair via Chemokine Induction - Lapi, Ioanna (Mar Drugs, 2021)
Restoring homeostasis following tissue damage requires a dynamic and tightly orchestrated sequence of molecular and cellular events that ensure repair and healing. It is well established that nutrition directly affects skin homeostasis, while malnutrition causes impaired tissue healing. In this study, we utilized fish sidestream-derived protein hydrolysates including fish collagen as dietary supplements, and investigated their effect on the skin repair process using a murine model of cutaneous wound healing. We explored potential differences in wound closure and histological morphology between diet groups, and analyzed the expression and production of factors that participate in different stages of the repair process. Dietary supplementation with fish sidestream-derived collagen alone (Collagen), or in combination with a protein hydrolysate derived from salmon heads (HSH), resulted in accelerated healing. Chemical analysis of the tested extracts revealed that Collagen had the highest protein content and that HSH contained the great amount of zinc, known to support immune responses. Indeed, tissues from mice fed with collagen-containing supplements exhibited an increase in the expression levels of chemokines, important for the recruitment of immune cells into the damaged wound region. Moreover, expression of a potent angiogenic factor, vascular endothelial growth factor-A (VEGF-A), was elevated followed by enhanced collagen deposition. Our findings suggest that a 5%-supplemented diet with marine collagen-enriched supplements promotes tissue repair in the model of cutaneous wound healing, proposing a novel health-promoting use of fish sidestreams.